Comparative Seismic Analysis of Fixed and Isolated Base RC Bare Frames with Plan Irregularity under Equivalent Static Loads - Crimsan Singh Negi; Dhiraj Pant (Momentum International Journal of Civil Engineering (MIJCE), 2026)
This study presents a comparative evaluation of the seismic response of mid-rise (G+4) reinforced concrete (RC) bare frame structures featuring plan irregularities, specifically L, I, and T-shaped configurations under fixed base and base-isolated conditions. These irregularities, typical in public buildings, lead to asymmetrical mass and stiffness distributions, affecting seismic performance. Six models were developed and analyzed using the Equivalent Static Method (ESM), with key parameters including base shear, storey drift, top-storey displacement, and fundamental time period. The results show that base isolation using rubber bearings effectively reduces base shear by 15-18%, although it increases overall system flexibility. Isolated models exhibited 44-45% higher top-storey displacements and 108-115% greater storey drifts compared to fixed-base counterparts. The fundamental time period also increased by approximately 40%, indicating enhanced energy dissipation and reduced structural stiffness. Among the plan configurations, I-shaped models experienced the highest base shear, while T-shaped structures performed best in terms of seismic efficiency. Despite excluding masonry infill and soil-structure interaction, the findings highlight the potential of base isolation to significantly enhance the seismic resilience of irregular RC buildings. The study recommends integrating base isolation in the design of geometrically irregular public buildings, particularly in high seismic zones, to improve safety and performance under earthquake loading.